Pengaruh Daya dan Waktu Terhadap Yield Hasil Ekstraksi Minyak Daun Spearmint Menggunakan Metode Microwave Assisted Extraction - Fitria Yulistiani; Rizka Khairiyyah Azzahra; Yulinda Alhay Nurhafshah (Jurnal Teknik Kimia dan Lingkungan, 2020)
Spearmint is one type of mint that contains essential oil with carvone (60-70%) as its main component. That component causes mint’s essential oil has antioxidant, antifungal and antibacteria properties. The traditional method to produce essential oil like steam distillation has long and energy consuming processes. The aims of this research were to investigate the influence of microwave power level (100, 180 and 300 Watt) and the extraction time (5, 10, 15 and 20 minutes) used Microwave Assisted Extraction to mint oil’s yield. Furthermore, characterization determined by oil’s colour, refractive index and density. The analysis of chemical component of mint oil was done using Gas Chromatography – Mass Spectrometry (GC-MS). The power level of microwave and extraction time influence to mint oil’s yield is proven in this research. The highest yield (5.17%) is generated at best variation of power and extraction time from the research are at 180 Watt and 15 minutes extraction time. The colour of mint oil is light yellow, refractive index value is 1.362 and density is 0.8758 gram/mL. The result of GC-MS showed that the major component of mint oil is 71% carvone.